Philippine medical thesaurus on anatomy cardiovascular and nervous systems in tagalog - Garcia, Maria Esperanza C. (2003)
Information is believed to be the new basic resource. Different areas of studies have created ways to mine, store, share, and even use information in numerous manners. And because of the diversity of these collections of processed and organized data, there is a growing need for a controlled vocabulary or authority list for easy retrieval.